A randomised controlled trial of artemether-lumefantrine versus artesunate for uncomplicated plasmodium falciparum treatment in pregnancy. - Mcgready, R; Tan, S; Ashley, E; Pimanpanarak, M; Viladpai-Nguen, J; Phaiphun, L; Wüstefeld, K; Barends, M; Laochan, N; Keereecharoen, L; Lindegardh, N; Singhasivanon, P; et al. (Public Library of Science, 2008)
BACKGROUND: To date no comparative trials have been done, to our knowledge, of fixed-dose artemisinin combination therapies (ACTs) for the treatment of Plasmodium falciparum malaria in pregnancy. Evidence on the safety and efficacy of ACTs in pregnancy is needed as these drugs are being used increasingly throughout the malaria-affected world. The objective of this study was to compare the efficacy, tolerability, and safety of artemether-lumefantrine, the most widely used fixed ACT, with 7 d artesunate monotherapy in the second and third trimesters of pregnancy. METHODS AND FINDINGS: An open-label randomised controlled trial comparing directly observed treatment with artemether-lumefantrine 3 d (AL) or artesunate monotherapy 7 d (AS7) was conducted in Karen women in the border area of northwestern Thailand who had uncomplicated P. falciparum malaria in the second and third trimesters of pregnancy. The primary endpoint was efficacy defined as the P. falciparum PCR-adjusted cure rates assessed at delivery or by day 42 if this occurred later than delivery, as estimated by Kaplan-Meier survival analysis. Infants were assessed at birth and followed until 1 y of life. Blood sampling was performed to characterise the pharmacokinetics of lumefantrine in pregnancy. Both regimens were very well tolerated. The cure rates (95% confidence interval) for the intention to treat (ITT) population were: AS7 89.2% (82.3%-96.1%) and AL 82.0% (74.8%-89.3%), p = 0.054 (ITT); and AS7 89.7% (82.6%-96.8%) and AL 81.2% (73.6%-88.8%), p = 0.031 (per-protocol population). One-third of the PCR-confirmed recrudescent cases occurred after 42 d of follow-up. Birth outcomes and infant (up to age 1 y) outcomes did not differ significantly between the two groups. The pharmacokinetic study indicated that low concentrations of artemether and lumefantrine were the main contributors to the poor efficacy of AL. CONCLUSION: The current standard six-dose artemether-lumefantrine regimen was well tolerated and safe in pregnant Karen women with uncomplicated falciparum malaria, but efficacy was inferior to 7 d artesunate monotherapy and was unsatisfactory for general deployment in this geographic area. Reduced efficacy probably results from low drug concentrations in later pregnancy. A longer or more frequent AL dose regimen may be needed to treat pregnant women effectively and should now be evaluated. Parasitological endpoints in clinical trials of any antimalarial drug treatment in pregnancy should be extended to delivery or day 42 if it comes later. TRIAL REGISTRATION: Current Controlled Trials ISRCTN86353884.